PENGARUH KOMISARIS INDEPENDEN, KOMITE AUDIT, KEPEMILIKAN INSTUTISIONAL DAN KEPEMILIKAN MANAJERIAL TERHADAP INTEGRITAS LAPORAN KEUANGAN (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia Tahun 2012-2014) - Daniel Oscar Savero; Azwir Nasir; Devi Safitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aimed to determine the influence of independent directors, audit committee, institutional ownership and managerial ownership on the integrity of the financial statement. Independent variables used in this study are independent directors, audit committee, institutional ownership and managerial ownership, while the dependent variable in this study is the integrity of the financial statement are measured using conservatism index (C-Score).Populations used in this study is manufacture companies listed on IDX 2012-2014 where the total population is used by 10 companies. The sampling technique used was purposive sampling technique in which the number of observations obtained this study was 30 (10x3). Data analysis conducted with multiple regression model with help of software SPSS version 20,0.Of the result of the testing that has been done, the partial regression test(t test) showed that the independent variables independent directors, audit committee, institutional ownership and managerial ownership which has a significant influence on integrity of the financial statement. Its mean if the independent variabel independent directors, audit comittee, institutional ownership and managerial ownership grows, its can make change on integrity of the financial statement. and if the independent directors, audit comittee, institutional ownership and managerial ownership is being low, its can make integrity of the financial statement be low too.Keywords :Independent Commissioners, Audit Commite, Institutional Ownership and Managerial Ownership, Integrity of the Financial Report.